Radar‐Detected Englacial Debris in the West Antarctic Ice Sheet. Issue 17 (10th September 2019) - Winter, Kate; Woodward, John; Ross, Neil; Dunning, Stuart A.; Hein, Andrew S.; Westoby, Matthew J.; Culberg, Riley; Marrero, Shasta M.; Schroeder, Dustin M.; Sugden, David E.; Siegert, Martin J.
Abstract: Structural glaci‐geological processes can entrain basal sediment into ice, leading to its transportation and deposition downstream. Sediments potentially rich in essential nutrients, like silica and iron, can thus be transferred from continental sources to the ocean, where deposition could enhance marine primary productivity. However, a lack of data has limited our knowledge of sediment entrainment, transfer, and distribution in Antarctica, until now. We use ice‐penetrating radar to examine englacial sediments in the Weddell Sea sector of the West Antarctic Ice Sheet. Radargrams reveal englacial reflectors on the leeside of nunataks and subglacial highlands, where Mie scattering analysis of the reflectors suggests particle sizes consistent with surface moraine sediments. We hypothesize that these sediments are entrained at the thermal boundary between cold and warm‐based ice. Conservative estimates of >130 × 10 9 kg of englacial sediment in Horseshoe Valley alone suggest that the ice sheet has significant entrainment potential unappreciated previously. Plain Language Summary: Glaciers can acquire and transport sediments rich in essential nutrients, like silica and iron, from the land to the ocean, where deposition may enhance biological productivity. Our ability to detect and map sediment‐rich ice in Antarctica has been hindered by technical limitations of geophysical equipment and data availability, until now. In this paper ice‐penetrating radar is used to detect sediments in the Weddell Sea sector of the West Antarctic Ice Sheet. We identify sediment near the glacial surface, and further down the ice column, along partially buried mountain ranges and bedrock hills beneath the ice. Our conservative estimates reveal >130 million metric tonnes of englacial sediment in a single valley. These sediments are entrained at the ice/bed interface and transported to mountain fronts and the coast by local and regional ice flow. Key Points: Ice‐penetrating radar reveals basal sediment reflectors in the West Antarctic Ice Sheet Basal thermal regimes promote sediment entrainment Once entrained, basal sediments are transported by regional ice flow